2004
DOI: 10.1086/386321
|View full text |Cite
|
Sign up to set email alerts
|

Sedation, Sucralfate, and Antibiotic Use Are Potential Means for Protection against Early-Onset Ventilator-Associated Pneumonia

Abstract: To examine risk factors for early-onset ventilator-associated pneumonia (EOP) in patients requiring mechanical ventilation (MV), we performed a prospective cohort study that included 747 patients. Pneumonia was defined as a positive result for a protected quantitative distal sample. EOP was defined as pneumonia that occurred from day 3 to day 7 of MV. Eighty patients (10.7%) experienced EOP. Independent predictors of EOP were male sex (odds ratio [OR], 2.06; 95% confidence interval [CI], 1.18-3.63), actual Gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 50 publications
2
27
1
6
Order By: Relevance
“…Previous studies [10,31] have found a significant association between coma and VAP. This association may be related to the frequent aspiration in patients with neurological impairment.…”
Section: S Aureusmentioning
confidence: 81%
“…Previous studies [10,31] have found a significant association between coma and VAP. This association may be related to the frequent aspiration in patients with neurological impairment.…”
Section: S Aureusmentioning
confidence: 81%
“…This disease leads to increase of mortality in patients, duration of hospitalization and therapeutic costs [9,10]. Rate of appearance of pneumonia caused by ventilator has been reported in a range from 7.5% to 45% in the various studies [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The database is specifically designed to record daily disease severity and the occurrence of iatrogenic events and nosocomial infections [1,[17][18][19][20][21]. Inclusion criteria for the study were MV for o2 days, started within 48 h after ICU admission, with an arterial oxygen tension/inspiratory oxygen fraction ratio (Pa,O 2 /FI,O 2 ) f300 during the first 2 days of MV with bilateral infiltrates with classic absence of clinical evidence of left atrial hypertension according to the protocol of each ICU.…”
Section: Study Design and Data Sourcementioning
confidence: 99%
“…MV duration, time in the ICU and hospital, and outcome at ICU and hospital discharge were recorded prospectively. Clinically suspected nosocomial pneumonia was routinely investigated using cultures of protected distal specimens, protected brushing or bronchoalveolar lavage, as previously described [2,18].…”
Section: Data Collectionmentioning
confidence: 99%